Development of Papercraft Visual Media On Grade IV Fraction Material In Elementary School - Firyani, Putri; Ninawati, Mimin (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
The lack of utilization of learning media makes it difficult for students to learn the concept of fractions, including students having difficulty understanding the teacher's explanation and difficulty performing calculations. Creating beautiful papercraft media to teach math is the driving force behind this research. The purpose of this research is to develop visual papercraft media and to find out whether visual papercraft media is feasible to be used as learning media in the Mathematics content in the classroom. This research uses the Research and Development (R&D) method using the 4-D model which goes through four stages, namely: 1. Define, 2. Design, 3. Development (Development), 4. Dissemination (Disseminate). Descriptive questionnaires were used for data collection. Students of SDN Cilincing 03 Pagi who are in grade IV participated as research subjects. This research was conducted by forming large groups and small groups. There were a total of 27 students from class IV B, with 10 students from class IV A forming the small group. The validation results from media experts and material experts showed that papercraft media is very suitable for teaching fractions. Media expert validation results reached 90% with a very feasible category, material expert results reached 91% with a very feasible category, and responses from 10 students in this study reached 94.9% with a very feasible category. In addition, responses from 27 students were at 94% with a very feasible category. It is concluded that papercraft media is a learning media that is very suitable for teaching fraction material in Mathematics subjects to grade IV elementary school students.